Dgp Cosmological Model with Generalized Ricci Dark Energy - Cruz-Marin, N; Aguilera-Martinez, y (Springer New York LLC, 2014)
The brane-world model proposed by Dvali, Gabadadze and Porrati (DGP) leads to an accelerated universe without cosmological constant or other form of dark energy for the positive branch (Formula presented.). For the negative branch (Formula presented.) we have investigated the behavior of a model with an holographic Ricci-like dark energy and dark matter, where the IR cutoff takes the form (Formula presented.), H being the Hubble parameter and ?, ? positive constants of the model. We perform an analytical study of the model in the late-time dark energy dominated epoch, where we obtain a solution for (Formula presented.), where rc is the leakage scale of gravity into the bulk, and conditions for the negative branch on the holographic parameters ? and ?, in order to hold the conditions of weak energy and accelerated universe. On the other hand, we compare the model versus the late-time cosmological data using the latest type Ia supernova sample of the Joint Light-curve Analysis (JLA), in order to constrain the holographic parameters in the negative branch, as well as rcH0 in the positive branch, where H0 is the Hubble constant. We find that the model has a good fit to the data and that the most likely values for (Formula presented.) lie in the permitted region found from an analytical solution in a dark energy dominated universe. We give a justification to use a holographic cutoff in 4D for the dark energy in the 5-dimensional DGP model. Finally, using the Bayesian Information Criterion we find that this model is disfavored compared with the flat (Formula presented.) CDM model. © 2014, The Author(s).